Corrective Culture and Organizational Climate as Determiners of Teachers Motivation in Schools - Argadinata, Hasan (Faculty of Education Universitas Negeri Malang, 2022)
Organizational climate has a rich, but largely unattainable, role in organizational development and increasing work motivation. Researchers looked at problems arising from different cultures and climates affecting management and motivation levels among teacher performance. This study examines the influence of climate and organizational culture on the motivation level of teachers who work in schools with the help of various previous research results compiled into the results of a literature review. In particular, organizational climate factors understand the environment, teamwork, management efficiency, participation, assessment and recognition, competence and commitment. These factors have been found to influence motivation and are considered to be multidimensional constructs. The results showed that most teachers carrying out their duties and functions have high work motivation if they are familiar with the culture and organizational climate deeply and for a long time.